2012
DOI: 10.7314/apjcp.2012.13.10.4967
|View full text |Cite
|
Sign up to set email alerts
|

Null Genotype of GSTT1 Contributes to Esophageal Cancer Risk in Asian Populations: Evidence from a Meta-analysis

Abstract: Background/Aims: Glutathione S-transferase T1 (GSTT1), a phase-II enzyme, plays an important role in detoxification of carcinogen electrophiles. Many studies have investigated the association between GSTT1 polymorphism and esophageal cancer risk in Asian populations, but its actual impact is not clear owing to apparent inconsistencies among those studies. Thus, a meta-analysis was performed to explore the effect of GSTT1 polymorphism on the risk of developing esophageal cancer. Methods: A literature search of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
1
7
0
Order By: Relevance
“…With regard to polymorphisms in the GSTT1 gene, this study supports findings of several other studies from regions with high ESCC incidence, including other Indian regions [34,35]. A meta-analysis also reported a significant association between GSTT1 polymorphism and ESCC risk in Asian populations (OR = 1.26, 95 %CI = 1.05-1.52) [36]. However, this association has not been supported by studies from low-incidence areas, including Japan and Europe [37].…”
Section: Discussionsupporting
confidence: 89%
“…With regard to polymorphisms in the GSTT1 gene, this study supports findings of several other studies from regions with high ESCC incidence, including other Indian regions [34,35]. A meta-analysis also reported a significant association between GSTT1 polymorphism and ESCC risk in Asian populations (OR = 1.26, 95 %CI = 1.05-1.52) [36]. However, this association has not been supported by studies from low-incidence areas, including Japan and Europe [37].…”
Section: Discussionsupporting
confidence: 89%
“…In Pakistan, regions adjacent to the cancer built extending from Quetta through Dera Ismail Khan into Khyber Pakhtunkhwa have high incidence rate as compared to other areas and some expert suggest it as the 'extension of the Asian cancer belt' (Figure 1) (Jamal, 2010). Many factors have been implicated in these areas in the etiology of the disease including environmental factors such as mineral contents of the soil; dietary factors such as diet low in fruits, vegetables and animal proteins; personal habits such as tobacco intake and alcoholism (Cortes and Villasenor, 1997;Sharma et al, 2011;Yi and Li 2012). Besides that, age, gender, poor socioeconomic status and genetic factors also contribute towards the disease (Mao et al, 2012;Amani et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For 51 SNPs identified by meta‐analysis, 38 SNPs had statistically significant association with EC or ESCC susceptibility . Meta‐analysis results showed that there were 27 SNPs associated with increased EC or ESCC risk, whereas 11 SNPs decreased the risk of EC or ESCC risk.…”
Section: Resultsmentioning
confidence: 94%